Pelatihan Strategi Pembelajaran Bahasa Inggris yang Menyenangkan di Sekolah Dasar - Reski, Reski; Ridwan, Ridwan; Ikhsan, Ikhsan; Rusdiah, Rusdiah (Journal of Comprehensive Science, 2025)
This community service activity was held by the joint collaboration of English Education Department of Universitas Sulawesi Barat with The Practitioners Community of SD Negeri 035 Bussu, Polewali Mandar. The purposes of this activity were to enhance the strategy of teaching English as well as to build up the motivation to teach English for elementary school students for the teachers who were members of The Sharing Good Practices Community that was organized by a number of teachers in Bussu village, Tapango district of Polewali Mandar regency. This activity was held online on December 11, 2024 and had several ideas to increase the strategies of teaching English for elementary school students as the result. A few of the proposed strategies were the use of internet-based platforms to teach English for elementary school students and the use of audio-visual media to encourage students to learn English more actively.